2020
DOI: 10.3390/jcm9030850
|View full text |Cite
|
Sign up to set email alerts
|

Cognition in Children with Arachnoid Cysts

Abstract: Background: This study aims to evaluate if children with temporal arachnoid cysts (AC) have cognitive symptoms and if neurosurgery improves these. Methods: A prospective case series study including consecutive pediatric patients with temporal AC. The children underwent neuroradiology, neuroopthalmologic evaluation, and a standard electroencephalography (EEG). Additionally, a neuropsychologist performed a standardized set of evaluations, with a one-year follow-up consisting of Weschler Intelligence Scale for Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Arachnoid cysts can be the focus of epileptic seizures (25). An increased seizure frequency had been described in the case of temporal cysts (30,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arachnoid cysts can be the focus of epileptic seizures (25). An increased seizure frequency had been described in the case of temporal cysts (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications demonstrated bene ts in various symptoms like seizures, headache and cognition after surgical attempts (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…[18] Recently, more evidences have shown that MFACs have a negative effect on general cognitive ability and that this impairment can be improved by surgery. [34,19,1] But the remarkable complications reported in recent years' studies hinder the pursuit of these functional improvements. The surgical techniques of MFAC fenestration have been demonstrated in numerous studies.…”
Section: Discussionmentioning
confidence: 99%
“…[30] Proptosis, contralateral paresis, seizures, developmental disorders, language disorders, delays in neuropsychomotor development, and attention deficits have been described in children with arachnoid cysts of the middle fossa, [3,20,31,38,39] with some studies reporting improvement in cognitive function after neurosurgical treatment. [38,40,41] On the other hand, other authors have also demonstrated no correlation between arachnoid cysts of the middle fossa, even higher volumes, and neurocognitive impairment in children. [31,42,43]…”
Section: Middle Fossa and Sylvian Fissurementioning
confidence: 99%